2013
DOI: 10.1021/jp400742q
|View full text |Cite
|
Sign up to set email alerts
|

Microwave Detection of Sulfoxylic Acid (HOSOH)

Abstract: Sulfoxylic acid (HOSOH), a chemical intermediate roughly midway along the path between highly reduced (H2S) and highly oxidized sulfur (H2SO4), has been detected using Fourier transform microwave spectroscopy and double resonance techniques, guided by new high-level CCSD(T) quantum-chemical calculations of its molecular structure. Rotational spectra of the two most stable isomers of HOSOH, the putative ground state with C2 symmetry and the low-lying C(s) rotamer, have been measured to high precision up to 71 G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 40 publications
0
15
0
Order By: Relevance
“…Intramolecular dehydration of 24 gives 25 which might exist in equilibrium with 23 , but the dehydration is likely kinetically slow. Theory predicts sulfoxylic tautomer to be the lowest energy tautomer in the gas phase [45] , but the ratio of sulfoxylic and sulfinic acid under our reaction conditions, as by trapped species 21 vs 23 / 25 , is 7:100. Thus the S(IV) oxidation state predominates, perhaps aqueous solvation favors the more acidic sulfinic form.…”
Section: Sulfoxylic Acid H 2 Somentioning
confidence: 73%
See 1 more Smart Citation
“…Intramolecular dehydration of 24 gives 25 which might exist in equilibrium with 23 , but the dehydration is likely kinetically slow. Theory predicts sulfoxylic tautomer to be the lowest energy tautomer in the gas phase [45] , but the ratio of sulfoxylic and sulfinic acid under our reaction conditions, as by trapped species 21 vs 23 / 25 , is 7:100. Thus the S(IV) oxidation state predominates, perhaps aqueous solvation favors the more acidic sulfinic form.…”
Section: Sulfoxylic Acid H 2 Somentioning
confidence: 73%
“…The dioxygenation product of H 2 S, H 2 SO 2 , may exist as sulfoxylic, 16 , sulfinic, 17 dihydrogen sulfone, 18 or the sulfhydryl peroxide, 19 , tautomer shown in Scheme 6 [45] . Theoretical calculations suggest that alcohol 16 is the most stable, and peroxide 19 is the least stable tautomer.…”
Section: Sulfoxylic Acid H 2 Somentioning
confidence: 99%
“…According to Tossell [29], only the presence of protonated species (OH)SO − in the original solution (with pH 11.5–12) would explain the presence of the 918 cm −1 peak and its disappearance upon acidification. Later, Crabtree and coworkers detected sulfoxylic acid using Fourier transform microwave spectroscopy and double resonance techniques, guided by new high-level CCSD(T) quantum chemical calculations of its molecular structure [30]. In accordance with earlier studies [29,31] their electronic structure calculations have shown that the lowest energy configurations of H 2 SO 2 in vacuum are rotamers of sulfoxylic acid (denoted S(OH) 2 ), where the protons are bound to each of the oxygen atoms.…”
Section: Sos As the Intermediates Of Hydrogen Sulfide Oxidationmentioning
confidence: 99%
“…110 It was proved by neutralization-reionization mass spectrometry that S(OH) 2 can survive in the gas phase on the time scale of microseconds. 104 Furthermore, S(OH) 2 was also identified and characterized by microwave spectroscopy, 111 while the HS(O)OH isomer has been detected in the solid phase by IR spectroscopy in irradiated H 2 S/SO 2 mixtures isolated in Ar matrices. 112 Regarding the third most stable isomer H 2 SO 2 , to the best of our knowledge, it has not been isolated so far experimentally.…”
Section: Introductionmentioning
confidence: 99%